Quality of life in patients with metastatic prostate cancer following treatment with cabazitaxel versus abiraterone or enzalutamide (CARD): an analysis of a randomised, multicentre, open-label, phase 4 study. Issue 11 (November 2020) - Fizazi, Karim; Kramer, Gero; Eymard, Jean-Christophe; Sternberg, Cora N; de Bono, Johann; Castellano, Daniel; Tombal, Bertrand; Wülfing, Christian; Liontos, Michael; Carles, Joan; Iacovelli, Roberto; Melichar, Bohuslav; et al.
Summary: Background: In the CARD study, cabazitaxel significantly improved radiographic progression-free survival and overall survival versus abiraterone or enzalutamide in patients with metastatic castration-resistant prostate cancer previously treated with docetaxel and the alternative androgen signalling-targeted inhibitor. Here, we report the quality-of-life outcomes from the CARD study. Methods: CARD was a randomised, multicentre, open-label, phase 4 study involving 62 clinical sites across 13 European countries. Patients (aged ≥18 years, Eastern Cooperative Oncology Group (ECOG) performance status ≤2) with confirmed metastatic castration-resistant prostate cancer were randomly assigned (1:1) by means of an interactive voice–web response system to receive cabazitaxel (25 mg/m 2 intravenously every 3 weeks, 10 mg daily prednisone, and granulocyte colony-stimulating factor) versus abiraterone (1000 mg orally once daily plus 5 mg prednisone twice daily) or enzalutamide (160 mg orally daily). Stratification factors were ECOG performance status, time to disease progression on the previous androgen signalling-targeted inhibitor, and timing of the previous androgen signalling-targeted inhibitor. The primary endpoint was radiographic progression-free survival; here, we present more detailed analyses of pain (assessed using item 3 on the Brief Pain Inventory-Short Form [BPI-SF]) and symptomatic skeletal events, alongside preplanned patient-reported outcomes, assessed using the Functional Assessment of Cancer Therapy—Prostate (FACT-P) questionnaire and the EuroQoL—5 dimensions, 5 level scale (EQ-5D-5L). Efficacy analyses were done in the intention-to-treat population. Pain response was analysed in the intention-to-treat population with baseline and at least one post-baseline assessment of BPI-SF item 3, and patient-reported outcomes (PROs) were analysed in the intention-to-treat population with baseline and at least one post-baseline assessment of either FACT-P or EQ-5D-5L (PRO population). Analyses of skeletal-related events were also done in the intention-to-treat population. The CARD study is registered with ClinicalTrials.gov, NCT02485691, and is no longer enrolling. Findings: Between Nov 17, 2015, and Nov 28, 2018, of 303 patients screened, 255 were randomly assigned to cabazitaxel (n=129) or abiraterone or enzalutamide (n=126). Median follow-up was 9·2 months (IQR 5·6–13·1). Pain response was observed in 51 (46%) of 111 patients with cabazitaxel and 21 (19%) of 109 patients with abiraterone or enzalutamide (p<0·0001). Median time to pain progression was not estimable (NE; 95% CI NE–NE) with cabazitaxel and 8·5 months (4·9–NE) with abiraterone or enzalutamide (hazard ratio [HR] 0·55, 95% CI 0·32–0·97; log-rank p=0·035). Median time to symptomatic skeletal events was NE (95% CI 20·0–NE) with cabazitaxel and 16·7 months (10·8–NE) with abiraterone or enzalutamide (HR 0·59, 95% CI 0·35–1·01; log-rank p=0·050). Median time to FACT-P total score deterioration was 14·8 months (95% CI 6·3–NE) with cabazitaxel and 8·9 months (6·3–NE) with abiraterone or enzalutamide (HR 0·72, 95% CI 0·44–1·20; log-rank p=0·21). There was a significant treatment effect seen in changes from baseline in EQ-5D-5L utility index score in favour of cabazitaxel over abiraterone or enzalutamide (p=0·030) but no difference between treatment groups for change from baseline in EQ-5D-5L visual analogue scale (p=0·060). Interpretation: Since cabazitaxel improved pain response, time to pain progression, time to symptomatic skeletal events, and EQ-5D-5L utility index, clinicians and patients with metastatic castration-resistant prostate cancer can be reassured that cabazitaxel will not reduce quality of life when compared with treatment with a second androgen signalling-targeted inhibitor. Funding: Sanofi.